Status, abundance and threats to waterbirds of the Great Vedaranyam Swamp, Point Calimere Wildlife Sanctuary (Ramsar Site), South-east coast of India - R, Manikannan; S, Asokan; A, Mohamed Samsoor Ali; G, Madhuramozhi (Journal of Research in Biology, 2011)
Totally 46 waterbird species were identified at the Great Vedaranyam Swamp of the Point Calimere Wildlife Sanctuary during October 2007 - March 2010. It included waterbird species representing 11 families and 5 orders comprising of winter migrants (30 species), residents (9 species) and seasonal migrants (7 species). The birds were classified into five categories in terms of abundance, namely, common (33%), very rare (30%), very common (15%), rare (11%) and occasional (11%). The highest number of species was observed during November–February (46 species) and lowest during July (5 species). The highest bird number was recorded in January 2010 (3,582 individuals). The commonest species is Greater Flamingo Phoenicopterus ruber (1,254 individuals). The major threats and a few management suggestions have been made on the improvements to the conservation of Great Vedaranyam Swamp of the Point Calimere Wildlife Sanctuary